Designing a Social Campaign on the Importance of Financial Education by Investing in Antam Gold Denominations Among Generation Z in Palembang City - Ardiansyah; Bobby Halim; Mukhsin Patriansah (Jurnal Multidisiplin Madani, 2022)
Generation Z is the generation whose births began in 1995 to 2010. The generation that has the principle of enjoying life in the present without worrying about life in the future. This can be seen by the choice of generation Z to shop rather than setting aside money for the future or investing. So with the design of a social campaign the importance of financial education with Antam's gold investment among generation Z in Palembang city to solve problems that occur and invite generation Z to starting investing so that in the future generation Z will be better financially, the method used in this design is using the 5W + 2H method in solving problems that occur. The result of this design is a social campaign about financial education about the importance of investing in Antam gold coins among generation Z in Palembang city through interactive media in conveying information about social campaigns and inviting generation Z to start investing in Antam gold coins